2018
DOI: 10.1002/adfm.201703581
|View full text |Cite
|
Sign up to set email alerts
|

Computational Chemistry‐Guided Design of Selective Chemoresponsive Liquid Crystals Using Pyridine and Pyrimidine Functional Groups

Abstract: We report computational chemistry-guided designs of chemoresponsive liquid crystals (LCs) with pyridine or pyrimidine groups that bind to metal cation-functionalized surfaces to provide improved selective responses to targeted vapor species (dimethylmethylphosphonate (DMMP)) over non-targeted species (water). We test the LC designs against experiments by synthesizing 4-(4-pentyl-phenyl)pyridine and 5-(4-pentyl-phenyl)-pyrimidine and quantifying LC responses to DMMP and water. Consistent with the computations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 27 publications
(66 citation statements)
references
References 49 publications
(66 reference statements)
2
64
0
Order By: Relevance
“…The first step in our approach used computational chemistry methods to select metal cations that exhibit oxidation‐state‐dependent binding interactions with mesogens . Specifically, we systematically studied the binding of benzonitrile (PhCN), a surrogate for the common mesogen 4‐cyano‐4′‐pentylbiphenyl (5CB; Scheme ) with a range of metal cations (as perchlorate salts; Table ).…”
Section: Methodsmentioning
confidence: 99%
“…The first step in our approach used computational chemistry methods to select metal cations that exhibit oxidation‐state‐dependent binding interactions with mesogens . Specifically, we systematically studied the binding of benzonitrile (PhCN), a surrogate for the common mesogen 4‐cyano‐4′‐pentylbiphenyl (5CB; Scheme ) with a range of metal cations (as perchlorate salts; Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Zuschriften showed that the cation surface density required to achieve ahomeotropic orientation of aLCdecreases with an increase in the strength of binding between the mesogen and metal cation binding site. [29] Guided by these prior design rules,w e investigated the use of LCs containing 4-(4-pentylphenyl)pyridine (PD,S cheme 1) [28] to generate ar esponse to Cl 2 . Table 1s hows that the binding energy of pyridine,t he surrogate for PD used in our computations,t oM n(ClO 4 ) 2 to be À1.75 eV,avalue that is 0.41 eV more negative than that of PhCN.Significantly,however,the binding energy of pyridine to MnO 2 is only À0.22 eV.Accordingly,these calculations led us to predict that LCs containing PD should transition from ahomeotropic orientation on Mn(ClO 4 ) 2 to aplanar orientation on MnO 2 upon exposure to Cl 2 with dynamics and sensitivity that exceed nitrile-containing LCs.B ecause PD does not form aL Ca sap ure component, we mixed it with 85 wt %nematic TL205 (Scheme 1) and confirmed mixing by using differential scanning calorimetry (Supporting Information, Figure S9).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In the absence of PD,TL205 does not assume ah omeotropic orientation on metal salt surfaces. [28,29] However,t he PD + TL205 mixture assumed homeotropic orientations on surfaces with densities of Mn 2+ as low as 3.7 AE 0.2 pmol mm À2 .T his contrasts to nitrile containing LCs such as 5CB that exhibit homeotropic orientations only when the surface density of Mn 2+ exceeds 7.0 AE 0.3 pmol mm À2 (see details in the Supporting Information). By using 3.7 AE 0.2 pmol mm À2 Mn(ClO 4 ) 2 and the PD + TL205 mixture,w e found that the response time of the LC to 1ppm Cl 2 was lowered to 4mins compared to 10 mins for 5CB on 10.6 AE 0.3 pmol mm À2 for 1ppm of Cl 2 (Figure 4; Supporting Information, Figure S7).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 2 more Smart Citations